Analisis Uji Jatuh Badan Pesawat R80 Dengan Metode Elemen Hingga - Ardianto, Adik Nofa Rochma Wahyu; , Agus Dwi Anggono, ST., M.Eng., Ph.D; , Ir. Agus Hariyanto, MT (2016)
In aerospace development, feasibility accidents design or crashworthiness is a major concern in aviation safety. Fuselage structure plays an important role in absorbing energy during an accident. The research aims are to determine drop test phenomenon on the fuselage, to investigate deformation occurred in the structure of the fuselage, to know the influence of the airframe falls position to the stress strain which occurred in the structure of the fuselage. This research was conducted by varying the fall angle of the fuselage in a vertical position or 0° and 15°. Fuselage design was modeled by using SolidWorks. Then the model is imported to the Abaqus for drop test simulation. From the simulation results, it can be obtained the phenomena of deformation on the structure of the fuselage when it comes in contact with the rigid ground. The high deformation occurs shows the structure capabilities in order to absorb the impact. It could be happened because the deformation is influenced by internal energy in and strain energy. The various positions shows the structure capability in order to withstand impact loads during periods of 4-8 seconds and the maximum deformation was reached in 12 seconds. The experiment on the vertical position and the position falls of 15° angle was delivered the highest stress strain. The stress was 483 MPa in struts section, 400.78 MPa in skin section, 358.28 MPa in the floor and 483 MPa in the cargo frame section.